(untitled) (Scottish Archaeological Internet Reports, 2010)
This chapter described the main archaeological features encountered during the excavation, and the artefactual and environmental evidence where appropriate. The results are prefaced by a summary of the main archaeological findings. At the end of the chapter is a brief discussion of how the archaeological results shed light on the main research questions posed at the beginning of the project.